THE CONTRIBUTION OF "LEADER" AND "LOCAL ACTION GROUPS" TO SUSTAINABLE REGIONAL DEVELOPMENT - Cristina Iuliana Petrovan (Maranda), Liliana Chihaia (Sava) (USV Annals of Economics and Public Administration)
The idea of sustainable regional development has only lately become popular in the countryside, even though rural areas always play a role in the economic and social prosperity of the area in which they are situated, no matter their current state of progress. The goal of closing economic and social inequalities gave rise to the LEADER program, which is based on the knowledge and abilities of local communities in identifying growth opportunities. Local Action Groups are the tangible answer, the materialization of the opportunities that nearby communities can harness to become part of the current European village growth strategy, which promotes the societal, cultural, and economic success of the locality. Utilizing a quantitative approach based on a questionnaire, we conducted this study to ascertain the current level of understanding among experts operating at the local action group level in Suceava County regarding the interaction between public-private partnerships (PPP) and sustainable regional development. The decision to consult these organizations is based on the aim of valuing local potential through the allocation of European financing to critical issues and challenges that promote sustainable regional development. Significant components that can improve the bond between public-private partnerships and sustainable regional development were found as a result of the quantitative study conducted using the questionnaire approach at the level of Suceava County's Local Action Groups.